'What if I was not adopted': transnational Chinese adoptee English teachers negotiating identities in Taiwan. Issue 2 (7th February 2023) - Lin, Shumin; Wu, Ming-Hsuan; Leung, Genevieve
ABSTRACT: While race in TESOL has gained traction in recent years, less research has focused on Asian American teachers working in Asian contexts, not to mention Chinese adoptees from the US working as English teachers in Asia. Drawing from our larger study on the work narratives of Asian Americans teaching English in Taiwan, this paper examines how Chinese adoptees negotiate their linguistic and cultural competencies and identities in Taiwan. We uncover the various forms of emotional labor that they experienced. Similar to other Asian American teachers, they also grappled with notions of authenticity and legitimacy in the ELT field in Taiwan. However, teaching in Taiwan provided Chinese adoptees with the opportunity to negotiate the roots and routes of transnational adoptee identities and simultaneously deploy their adoptee identities as pedagogical tools for teaching about racial and family diversity, which complicates and extends research on racial identities as pedagogy in ELT. It is inevitable that their racial identity and transracial family makeup are invoked, and they are confronted to take action on it. The process can be laborious, yet teaching students about diversity through these adoptees' own vantage points also constitutes their professional identity as a competent teacher.